Photography, Anthropology of - Morton, C (Wiley, 2018)
This entry charts the emergence of the anthropology of photography as a distinctive strand of recent anthropological inquiry, contextualizing the initial intellectual impetus for it and the academic contexts within which it emerged; describes the major areas of inquiry to date, as well as key areas of current research and theory, and the changing landscape of the study in the context of rapid social and technological change; and provides an overview of likely future areas of ethnographic and theoretical investigation. The two key strands of the anthropology of photography are discussed, namely the study of photographs as historical documents and as sources for new types of anthropological history writing, and the ethnographic study of indigenous photographic cultures, set within local and global visual systems of communication.